2000
DOI: 10.1242/jcs.113.22.4087
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rb family proteins, focal adhesion proteins and protein synthesis in senescent morphogenesis induced by hydrogen peroxide

Abstract: Early passage human diploid fibroblasts develop senescent morphology prematurely within a week after a 2-hour pulse treatment with low or mild dose H(2)O(2). We test here the role of cell cycle checkpoints, cytoskeletal proteins and de novo protein synthesis in senescent morphogenesis following H(2)O(2) treatment. H(2)O(2) treatment causes transient elevation of p53 protein and prolonged inhibition of Rb hyperphosphorylation. Expression of human papillomaviral E6 gene prevented elevation of p53 but did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Although the signal was weak in the green channel, this might be able to detect acid lysosomal β-Gal. The change in cell morphology because of cellular senescence is characterized by an enlarged, flattened, and irregular shape . These morphological changes were observed in many cells after the treatment using H 2 O 2 (Figure S9).…”
Section: Results and Discussionmentioning
confidence: 97%
“…Although the signal was weak in the green channel, this might be able to detect acid lysosomal β-Gal. The change in cell morphology because of cellular senescence is characterized by an enlarged, flattened, and irregular shape . These morphological changes were observed in many cells after the treatment using H 2 O 2 (Figure S9).…”
Section: Results and Discussionmentioning
confidence: 97%
“…Along with these responses, interestingly, a significant thickening of individual SFs is induced in senescent cells. It remains, however, controversial whether senescence leads to thicker or thinner SFs ( Chen et al. , 2000 ; Nishio and Inoue, 2005 ), despite their inherent connection to cell morphology and migration ( Hotulainen and Lappalainen, 2006 ; Meng and Takeichi, 2009 ; Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle analysis revealed that TSA at 100 nM/L concentration caused an arrest in cell cycle at G 0 /G 1 phase (Figure 4b), possibly through the activation of p53-and p21mediated pathways (Figure 4e-g). The observed morphological changes are reported to be typically associated with cellular senescence (Chen et al, 2000), and hence, we assumed that the inhibition of cell proliferation and changes in cell shape may precede cell senescence. Therefore, we extended our treatment period up to 5 days and did not find any increase in SA-β-gal activity, confirming there was no occurrence of cellular senescence (Figure 4d-g).…”
Section: Effect Of Hdaci On Cell Viability Hdac Activity and Histone ...mentioning
confidence: 99%